Experimental studies on the combustion characteristics and performance of a DI diesel engine using kapok oil methyl ester/diesel blends. (2016) - Asokan, M.A.; Vijayan, R.; Prabu, S. Senthur; Venkatesan, N.
The present study shows the biodiesel produced from the kapok oil through transesterification process blended with diesel. The kapok oil methyl ester (KOME) blends (B20, B30, B40 and B100) are tested in the single cylinder direct injection (DI) diesel engine. The performance of B30 blend matches closer to diesel among the blends and also its brake specific fuel consumption (BSFC) and exhaust gas temperature (EGT) were found to be 1.9% and 3.1% higher than the diesel where as brake thermal efficiency (BTE) of all blends is almost closer to diesel. The combustion characteristics of cylinder pressure and heat release rate coincided with the diesel fuel. At 100% load the emission characteristics of carbon monoxide (CO), hydrocarbon (HC) and smoke opacity of B100 were decreased by 23.33%, 40% and 45.53% respectively compared with diesel, where as nitrogen oxide (NOX) slightly increases by 3.5%. In future, KOME will find a place among biodiesel fuels. [Received: March 22, 2014; Accepted: November 15, 2014]